Performance optimization of PERC solar cells based on laser ablation forming local contact on the rear - Wu, Hao; Zhao, Shikai; Hong, Jiaqi; Zou, Dingsen; Hu, Kaixiang; Zhu, Ping; Chen, Yizhan (High temperature materials and processes, 2024)
To improve the photoelectric conversion efficiency ( ) of the solar cell, a green wavelength (532 nm) laser source in a nanosecond range was used to ablate the passivated emitter and rear cell (PERC) to form the contact holes. If the laser ablation hole opening process was not set properly, the diameter or the external expansion of holes would be too large, causing the decline of the PERC performance. The Gaussian distribution of the laser is regulated by the output power ( ) and the repetition frequency ( ) of the incident pulse laser, so that the optimized morphology of holes is obtained on the back of the PERC solar cells. After the contact holes are screen printed by the aluminum paste, the local back surface field is finally formed. The experimental results showed that the outward expansion decreases obviously with the increase of laser . Second, the spacing of the holes decreases with the increase of the laser . It was found that under the laser of 33.0 W and of 1,400 kHz, the of the industrial PERC solar cells was the highest. The Quokka simulations indicated that small outward expansion, small diameter, and long spacing of holes would further decrease the recombination parameter in the rear surface. With the optimized morphology of contact holes and the low contact resistance, the PERC cell’s calculated and improvements were 6.5 mV and 0.48%, respectively, which was verified with experimental findings.